Library lion - Knudsen, Michelle; Hawkes, Kevin (Cambridge, Mass. : Candlewick Press, 2006)
A lion starts visiting the local library but runs into trouble as he tries to both obey the rules and help his librarian friend.
Keywords: Lions -- Fiction; Libraries -- Fiction; Obedience -- Fiction